Parasites of reptiles in Iran (1922–2023): A literature review - Alireza Sazmand; MohammadParsa Miadfar; Georgiana Deak; Mohammad Babaei; Jairo A. Mendoza-Roldan; Domenico Otranto (International Journal for Parasitology: Parasites and Wildlife)
Reptiles are among the most diverse groups of animals, inhabiting nearly all continents and environments. Understanding their parasite biodiversity has garnered significant interest, particularly from a One Health perspective. Although the highly diverse reptile fauna of Iran, comprising 272 species i.e. 89 snakes (Serpentes), 171 lizards (Sauria), 8 turtles, 2 tortoises (Testudines), 1 crocodile (Crocodilia), and 1 worm-lizard (Amphisbaenia), there is a shortage of information about parasites. The present review is a compilation of 62 studies published from 1922 to August 2024. We present information on 56 species of reptiles from five groups (amphisbaenians, crocodiles, testudines, snakes, and lizards) and 98 parasitic taxa belonging to different protozoa and metazoa i.e. nematodes, cestodes, trematodes, acanthocephala, leeches, ticks, mites, and myiasis -producing flies. Although 63 taxa were diagnosed at the species level, 35 parasite taxa were only reported at the genus or family levels. Reviewing the literature, we found a paucity of information about endemic reptiles several of which are vulnerable species. Considering that some of the detected parasites e.g. Cryptosporidium and amoebae have serious clinical and/or public health threats molecular diagnostic techniques are needed for precise identification and understanding of the epidemiology and the potential zoonotic implications associated with parasites of reptiles. There is also a need to understand the exact distribution and host-parasite associations in different reptilian species present in Iran including the role of the reptiles as intermediate and reservoir hosts.